The Influence of Implementation of Corporate Social Responsibility, Profitability on Financial Performance with Company Size as a Moderating Variable in Indonesian Pharmacy Industry Companies Listed on the Indonesia Stock Exchange in 2018-2022 - Jaelani, Mohammad; Abbas, Yeni Elfiza; Solihin, Solihin (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
This research is a quantitative study that aims to understand how the implementation of Corporate Social Responsibility, and profitability affects financial performance with company size as a moderating variable in pharmaceutical industry companies listed on the Indonesia Stock Exchange in 2018-2022. The number of samples in this study was 8 pharmaceutical companies using the purposive sampling method with secondary data obtained from the company's annual report using the SEM-PLS analysis tool with the SmartPLS program. The results of the hypothesis analysis show that CSR has a positive and significant effect on financial performance as well as Profitability has a positive and significant effect on financial performance. Company size strengthens the relationship between CSR and financial performance but is not significant. Company size weakens the relationship between profitability and financial performance but is not significant.